2018
DOI: 10.1093/nar/gky037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of partially and fully chemically-modified siRNA in conjugate-mediated delivery in vivo

Abstract: Small interfering RNA (siRNA)-based drugs require chemical modifications or formulation to promote stability, minimize innate immunity, and enable delivery to target tissues. Partially modified siRNAs (up to 70% of the nucleotides) provide significant stabilization in vitro and are commercially available; thus are commonly used to evaluate efficacy of bio-conjugates for in vivo delivery. In contrast, most clinically-advanced non-formulated compounds, using conjugation as a delivery strategy, are fully chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
165
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 48 publications
(61 reference statements)
6
165
0
Order By: Relevance
“…The siRNAs used in these studies were fully chemically modified for maximal stability and minimal innate immune activation as described (see Figure 1a and Methods). We and others have recently shown that full chemical stabilization is essential for conjugated-mediated delivery [19][20][21] . The chemical compositions of lipids had a profound effect on the hydrophobicity of lipid-siRNA, based on retention time in reversed-phase HPLC 36 , which ranged from 1 to 12.2 minutes (Figure 1b).…”
Section: Synthesis Of Conjugated Sirnas Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The siRNAs used in these studies were fully chemically modified for maximal stability and minimal innate immune activation as described (see Figure 1a and Methods). We and others have recently shown that full chemical stabilization is essential for conjugated-mediated delivery [19][20][21] . The chemical compositions of lipids had a profound effect on the hydrophobicity of lipid-siRNA, based on retention time in reversed-phase HPLC 36 , which ranged from 1 to 12.2 minutes (Figure 1b).…”
Section: Synthesis Of Conjugated Sirnas Librarymentioning
confidence: 99%
“…Indeed, unmodified siRNAs are rapidly degraded and cleared from circulation by kidney filtration, leading to minimal bioavailability in tissues 12 . Thus, full chemical stabilization of siRNAs is essential for conjugate-mediated delivery 19 . The clinical success of GalNAc conjugated siRNAs was only achieved when the siRNAs are extensively modified 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…GalNAc‐conjugated siRNA, which drives receptor‐mediated uptake by hepatocytes, is another promising candidate for delivery with machine perfusion to the liver. GalNAc‐conjugated siRNAs are fully modified using an alternating 2’‐fluoro, 2’‐O‐methylation pattern to improve stability . Other 3’ lipid modifications to siRNA can drastically change distribution patterns in liver uptake, with the most lipophilic capable of uniformly penetrating mouse liver tissue without interrupting the siRNA’s ability to interact with RISC machinery (Fig.…”
Section: Machine Preservation: a New Ex Vivo Delivery System Of Rnai mentioning
confidence: 99%
“…GalNAc-conjugated siR-NAs are fully modified using an alternating 2'-fluoro, 2'-O-methylation pattern to improve stability. (47,57,58) Other 3' lipid modifications to siRNA can drastically change distribution patterns in liver uptake, with the most lipophilic capable of uniformly penetrating mouse REVIEW ARtIclE | 149 liver tissue without interrupting the siRNA's ability to interact with RISC machinery (Fig. 2).…”
Section: Machine Preservation: a New Ex Vivo Delivery System Of Rnai mentioning
confidence: 99%
“…In order to define design parameters for optimizing therapeutic oligonucleotide delivery, we investigated the influence of structurally diverse lipids on conjugate-mediated siRNA biodistribution, efficacy, and safety in vivo. These studies were enabled by the use of a clinicallyvalidated, chemically-modified siRNA scaffold that is nuclease resistant and metabolically stable 8 . Here, we demonstrate that lipid conjugation modulates the hydrophobicity of hsiRNA.…”
Section: Introductionmentioning
confidence: 99%